EFEK HETEROSIS DAN AKSI GEN UKURAN BUAH PADA HIBRIDA PEPAYA - Tri Budiyanti (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2016)
Fruit size is an important character in determining the quality of papaya fruit. Domestic consumers prefer small or medium size papaya fruit, while for the desirable fruit slices are large one. Assembly papaya varieties based on fruit size can be done through conventional breeding. The objectives of this study were to determine the effects of heterosis and gene action on the fruit size character of the papaya hybrid. The research was conducted at KP. Sumani Tropical Fruit Research Institute, Solok, West Sumatra in 2010-2011. This research used a randomized block design with 25 treatments (20 hybrids and five elders papaya) and repeated three times. The results showed that in general the heterosis effect on fruit size (weight, length and girth of the fruit) was found below 50%. Heterosis effect can decrease and increase the size of the fruit because the value is negative and positive. The negative excess of dominant gene action resulting in smaller sizes of F1 than the average of both parents or youngest parents. Therefore, crosssing BT3 x BT2 had the smallest fruit size. Positive excess of dominant gene action i.e crossing BT1 x D, BT4 x BT1 and D x BT3 resulted in bigger fruit size than two parents. Keywords: Gene action, Heterosis, Hybrid, Papaya